2017
DOI: 10.1111/jbi.13094
|View full text |Cite
|
Sign up to set email alerts
|

African origin and global distribution patterns: Evidence inferred from phylogenetic and biogeographical analyses of ectomycorrhizal fungal genus Strobilomyces

Abstract: Aim: The ectomycorrhizal genus Strobilomyces is widely distributed throughout many parts of the world, but its origin, divergence and distribution patterns remain largely unresolved. In this study, we aim to explore the species diversity, distribution and evolutionary patterns of Strobilomyces on a global scale by establishing a general phylogenetic framework with extensive sampling.Location: Africa, Australasia, East Asia, Europe, North America, Central America and Southeast Asia. Methods:The genealogical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 59 publications
(95 reference statements)
8
39
0
Order By: Relevance
“…In the genus Hydnum , it was found that one sample from Papua New Guinea is nearly identical to some Chinese samples [ 70 ]. More recently Han et al [ 73 ] showed at least three independent dispersal events for ancestors of Strobilomyces from Southeast Asia to Australasia. Considering the relatively low host specificity of Multifurca species or species pairs [ 3 , 16 , 19 ] we postulate that the dispersal of M .…”
Section: Discussionmentioning
confidence: 99%
“…In the genus Hydnum , it was found that one sample from Papua New Guinea is nearly identical to some Chinese samples [ 70 ]. More recently Han et al [ 73 ] showed at least three independent dispersal events for ancestors of Strobilomyces from Southeast Asia to Australasia. Considering the relatively low host specificity of Multifurca species or species pairs [ 3 , 16 , 19 ] we postulate that the dispersal of M .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that three EcMF lineages with a worldwide distribution (/russula-lactarius, /clavulina, and /inocybe) all originated in the tropics [4,102,103]. Additionally, Li et al [104] indicated that Strobilomyces might have originated in Africa during the early Eocene and then spread to Southeast Asia through the boreotropical forest; during the Oligocene, Strobilomyces was dispersed from Southeast Asia northward and southward to East Asia and Australasia, respectively; and during the Miocene, Strobilomyces migrated across the Bering land bridge, from East Asia to North America, and then was dispersed from the Asian continent to Japan through the East China Sea basin. At the same time, the climatic changes from the middle Miocene to the present might have driven the separation and differentiation between the regions [104].…”
Section: Temporal Evolution Patterns and Community Assembly Mechanismsmentioning
confidence: 99%
“…Additionally, Li et al [104] indicated that Strobilomyces might have originated in Africa during the early Eocene and then spread to Southeast Asia through the boreotropical forest; during the Oligocene, Strobilomyces was dispersed from Southeast Asia northward and southward to East Asia and Australasia, respectively; and during the Miocene, Strobilomyces migrated across the Bering land bridge, from East Asia to North America, and then was dispersed from the Asian continent to Japan through the East China Sea basin. At the same time, the climatic changes from the middle Miocene to the present might have driven the separation and differentiation between the regions [104]. Dispersion has played a crucial role in the formation of the current distribution pattern of Strobilomyces, and during its migration process across different continents, there was a shift in host plants from Dipterocarpaceae to Pinaceae and Fagaceae in East Asia and the northern temperate regions and then to Myrtaceae and Nothofagaceae in Oceania [86,104].…”
Section: Temporal Evolution Patterns and Community Assembly Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to morphological characters, host tree species and geographic distribution can be of help in delimiting species within ectomycorrhizal genera such as Catathelasma. Indeed, mycorrhizal host association and geographic separation could contribute to fungal speciation as host-shift events can provide ecological opportunities for the diversification of ectomycorrhizal fungi (Cui et al 2016(Cui et al , 2018Han et al 2018;Sato et al 2017;Sánchez-García et al 2016).…”
Section: Taxonomymentioning
confidence: 99%